PENGARUH INTELLECTUAL CAPITAL, INNOVATION CAPABILITY, DAN MARKETING CAPABILITY TERHADAP FINANCIAL PERFORMANCE - Natalia Permataria Kandari; Sarce Elsye Hatane (Business Accounting Review, 2016)
This study aimed to examine the direct and significant affect of intellectual capital, innovation capability, and marketing capability to financial performance in banking company in Surabaya. This study used a quantitative approach, and the data were obtained by distributing questionnaires to banks company in Surabaya and processed by using smartPLS software. This study showed that there was positive and significant relationship of intellectual capital, innovation capability, and marketing capability to financial performance in banking company in Surabaya